Exploring the Lived Experiences of Individuals With Spinal Cord Injury During the COVID-19 Pandemic - Eleni M. Patsakos MSc; K. Aly Bailey PhD; David S. Ditor PhD (SAGE Publishing, 2024)
The global spread of severe acute respiratory syndrome coronavirus 2019 (COVID-19) has affected over 100 countries and has led to the tragic loss of life, overwhelmed health care systems and severely impacted the global economy. Specifically, individuals living with spinal cord injury (SCI) are particularly vulnerable during the COVID-19 pandemic as they often face adverse impacts on their health, emotional well-being, community participation, and life expectancy. The objective of this study was to investigate the lived experience of individuals with SCI during the COVID-19 pandemic in Ontario, Canada. An exploratory design with a qualitative descriptive approach was used to address the study objective. Nine semi-structured interviews were conducted with individuals with traumatic and non-traumatic SCI (37-69 years, C3-L5, AIS A-D, and 5-42 years post-injury). Using reflexive thematic analysis, the following themes were created: (1) Caregiver exposure to COVID-19; (2) Staying physically active in quarantine; (3) Living in social isolation; (4) Difficulty obtaining necessary medical supplies; (5) Access to health services and virtual care during COVID-19; and (6) Fighting COVID-19 misinformation. This is one of the first studies to explore the impact of COVID-19 on individuals living with SCI in Ontario. This study contributes to a greater understanding of the challenges faced by individuals living with SCI and provides insight into how to better support and respond to the specific and unique needs of individuals with SCI and their families during a national emergency or pandemic.